2001
DOI: 10.1002/jctb.369
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction of Zn(II) by Cyanex 923 and its application to a solid‐supported liquid membrane system

Abstract: The extraction of zinc(II) by Cyanex 923 (phosphine oxides mixture) in Solvesso 100 from hydrochloric acid solution has been investigated. The extraction reaction is exothermic. The numerical analysis of metal distribution data suggests the formation of ZnCl 2 . L 2 ,HZnCl 3 . 2L and H 2 ZnCl 4 . 2L(L = ligand) in the organic phase with formation constants K ext = 4.1,5.6 Â 10 9 and 6.7 Â 10 9 , respectively. The results obtained for zinc(II) distribution have been implemented in a solid-supported liquid membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In this context, the use of ultrasound can be an excellent alternative to minimize sample preparation [3][4][5] and to avoid solvent extraction, 6,7 because its energy facilitates and accelerates some analytical steps, permitting less time consumption and decreasing the cost per analysis. Besides these characteristics, accuracy, precision, and handless manipulation can be achieved when ultrasound-assisted extraction methods are used.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of ultrasound can be an excellent alternative to minimize sample preparation [3][4][5] and to avoid solvent extraction, 6,7 because its energy facilitates and accelerates some analytical steps, permitting less time consumption and decreasing the cost per analysis. Besides these characteristics, accuracy, precision, and handless manipulation can be achieved when ultrasound-assisted extraction methods are used.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by taking in to account the fact that Cu, Ni, Sn and Pb exist as cationic species at 2.0 mol/dm 3 HCl concentration whereas gold and zinc exist in complex forms which are adsorbed by Cyanex 923 as reported. 24,33,36) For exploring the separation condition between gold and zinc, the adsorption study of gold has been carried out separately from its synthetic solution containing 5 mg Au/ dm 3 at 2.0 M acidity. The results showed that almost gold (99.5%) was adsorbed on SIR within 1,800 s and ratio 25 cm 3 /g (aqueous/resin).…”
Section: Adsorption Of the Other Metals By The Sirmentioning
confidence: 99%
“…The solvation reagent Cyanex-923 has proved its effectiveness in the separation of hazardous metals and mineral acids from various types of aqueous solutions (Alguacil and López, 1996;Alguacil and Martínez, 2001;Gupta et al, 2002;Regel et al, 2001;Rickelton, 1999;Saji et al, 1998;Wang et al, 2002), in which the stripping operation is more easily achieved than by the use of amine extractants (Regel et al, 2001;Wolters et al, 2002). Few data are available in the literature about considering liquid-liquid extraction in the treatment of stainless steel rinse waters, and thus the objective of this report is to study the factors that influence the extraction with Cyanex-923 of iron(III), HNO 3 , and HF and to determine the best conditions of their coextraction and selective stripping, with the aim of contributing to the body of research concerning extraction-based methods for recovering metals and acids from these wastewaters, with the consequent economic and environmental benefits.…”
Section: Introductionmentioning
confidence: 97%